Risk factors sharp injury among healthcare workers in Sleman State Hospital Yogyakarta province Indonesia - Sani Rachman Soleman; Taufiq Nugroho (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background : The sharp injury is the most burden problem among healthcare workers. The prevalence slightly increased as consequences spreading blood-borne pathogen. Some researchers had found several variables associated sharp injury among medical workers in the hospital. Objective : The objective of this research was to identify variables that significantly correlated sharp injury among healthcare workers in Sleman State Hospital, Yogyakarta Province, Indonesia. Methods : A cross-sectional study was conducted with total sampling as the method to collect respondents. Total population including a doctor, nurse, midwife, laboratory assistant has been selected based on inclusion criteria such as length of work more than one year and approved to be respondents, amounted 133 samples research. The analysis used chisquare for bivariate and logistic regression test for multivariate. Results : There were nine variables had identified that were age, gender, the level of education, the length of work, salary, occupation, employment status, body mass index, and the marital status. According chi-square analysis obtained gender, the level of education, salary, occupation, employment status and body mass index which were significantly correlated sharp injury (p-value > 0.05). Therefore, only two variables based on logistic regression had statistically related sharp injury. Those variables were salary <1.388.000 IDR (p-value 0.008, aOR 0.135, CI 0.031- 10.594) and abnormal body mass index (p-value 0.000, aOR 6.218, CI 2.552-15.147). Conclusion : In summary, there were two variables had correlated sharp injury among healthcare workers in Sleman state hospital Yogyakarta province, Indonesia; salary and body mass index.